2009
DOI: 10.1073/pnas.0902659106
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and pharmacological inhibition of JNK ameliorates hypoxia-induced retinopathy through interference with VEGF expression

Abstract: Many ocular pathologies, including retinopathy of prematurity (ROP), diabetic retinopathy, and age-related macular degeneration, result in vision loss because of aberrant neoangiogenesis. A common feature of these conditions is the presence of hypoxic areas and overexpression of the proangiogenic vascular endothelial growth factor (VEGF). The prevailing current treatment, laser ablation of the retina, is destructive and only partially effective. Preventive and less destructive therapies are much more desirable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
60
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 46 publications
(50 reference statements)
2
60
1
1
Order By: Relevance
“…The decrease of VEGF in JNK1-deficient mice was expected, as JNK1 regulates VEGF expression under different stimuli such as hypoxia and inflammation (13). However, our data further suggest that JNK1 may also be involved in the initial stages of AMD.…”
Section: Discussionsupporting
(Expert classified)
See 1 more Smart Citation
“…The decrease of VEGF in JNK1-deficient mice was expected, as JNK1 regulates VEGF expression under different stimuli such as hypoxia and inflammation (13). However, our data further suggest that JNK1 may also be involved in the initial stages of AMD.…”
Section: Discussionsupporting
(Expert classified)
“…Interestingly, it was shown that reactive oxygen species (ROS) cause JNK activation and cell death (12). We also recently showed that JNK1 is a critical factor in hypoxia-induced retinal VEGF production and that it promotes hypoxia-induced pathological angiogenesis (13). Thus, JNK1 might play a key Author contributions: M.K.…”
mentioning
confidence: 99%
“…In view of these observations, it is conceivable that VEGF or hypoxia-induced cPLA 2 phosphorylation may not require MAPK activation. Nonetheless, studies from our laboratories as well as others have shown a role for MAPKs such as JNK1 in the regulation of retinal angiogenesis (50,51). Based on these observations, it is probable that although both cPLA 2 and MAPKs are required for VEGF or hypoxia-induced retinal angiogenesis, they appear to be acting independently of each other in response to these agonists/conditions.…”
Section: Discussionmentioning
confidence: 77%
“…The observation that JNK was activated in ischemic neurons highlighted its potential involvement in the apoptotic process following cerebral ischemia (Borsello et al 2003).MAPKs activation has also been investigated in retinas after ischemia. Zhang et al first made the observation that both JNK and p38 activation could be attenuated by ischemic preconditioning, suggesting that these two MAPKs were implicated in the deleterious effects induced by ischemia in the retina (Zhang et al 2002).The use of D-JNKi provided a significant protection against neuronal loss after optic nerve crush in mice and in a model of retinopathy of prematurity (Tezel et al 2004;Guma et al 2009). …”
Section: Introductionmentioning
confidence: 95%